(:unas) unassigned - Chrysostomou, Christis (My University, 2019)
Based on information that Saint Andreas Monastery in the occupied part of Cyprus was facing structural integrity problems, a three-member team consisting of an architect and two structural engineers went to the Monastery with the United Nations and performed a visual inspection and took pictures. A report was prepared based on this information, which was used as the basis in the effort for the renovation of the Monastery.